Key factors and timing patterns in the tennis forehand of different skill levels - Landlinger, J.; Lindinger, S.; Stöggl, T.; Wagner, H.; Müller, E. (Journal of Sports Science & Medicine, 2010)
The main purpose of the present study was to quantify and compare selected kinematic variables and their timing during the tennis forehand of different skill levels. An eight-camera 400 Hz, Vicon motion analysis system recorded kinematic data of six ATP- professionals (elite) and seven high performance (HP) players when shots were played cross court and down the line. Timing of the maximum angles, linear and angular velocities was measured prior to and after impact. A total of twelve strokes per subject were analyzed from the beginning to the end of horizontal racquet movement. Significant differences (p < 0.01) and large effect sizes were observed between elite and HP players in the timing of maximum pelvis (-0.075 ± 0.008 vs. -0.093 ± 0.012 s) and trunk angular velocities (-0.057 ± 0.004 vs. -0.075 ± 0.011 s) before impact. The elite group showed a tendency (p < 0.05) towards higher peak horizontal shoulder (3.0 ± 0.4 vs. 2.5 ± 0.4 m·s-1) and racquet velocities (33.1 ± 2.4 vs. 31.1 ± 1.9 m·s-1) compared to the HP players. Depending on the situation (cross court vs. down the line), different peak hip, racquet and separation angles were found for both groups. Similar peak values were detected between groups for maximum angular velocities and displacement of key variables that had been selected for analysis. The findings of this study can be vital for successful player development, improved performance or injury prevention. The later occurrence of maximum angular pelvis and trunk rotations were the main reasons for the tendency towards higher horizontal shoulder and racquet velocities in the elite group.